“The national need of sympathy": valor y enseñanza del español como lengua extranjera en Estados Unidos a comienzos del siglo xx - Albert Ferrando, Lorena (El Colegio de México, 2023)
The two most frequent strategies employed in the debate on the role of foreign languages in the United States at the end of the nineteenth century were: The defense of the pragmatic value of the languages for matters concerning US foreign policy, and the vindication of the cultural tradition linked to the language to be learnt. In the case of Spanish, a third strategy was also brought to bear: The articulation of a panamerican fraternity varying according to the capacity of each individual language to encourage a sympathetic understanding between peoples. This text analyzes the influence on this moral argument of the different nuances of the term sympathy.